A ALTERNATIF PENYELESAIAN SENGKETA SECARA ARBITRASE MELALUI BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK): Penyelesaian Sengketa Secara Arbitrase melalui Badan Penyelesaian Sengketa Konsumen (BPSK) - Ananda, Saqinaya (Fakultas Hukum Universitas Muhammadiyah Palu, 2024)
Disputes arise due to various reasons and underlying problems. These consumer disputes occur due to violations of consumer rights. Judicially, consumer dispute resolution can be carried out through court or outside court, with the provisions regulated in the Consumer Protection Law Number 8 of 1999 and Based on the Decree of the Minister of Industry and Trade of the Republic of Indonesia Number: 350/MPP/Kep/12/2001 concerning Implementation Duties and Authorities of the Consumer Dispute Resolution Agency of the Minister of Industry and Trade. BPSK as an out-of-court consumer dispute resolution body that carries out arbitration functions is expected to provide legal certainty in resolving consumer disputes. The decision made by BPSK is final and binding, so the BPSK decision cannot be submitted for legal action again, according to the settlement method chosen by the consumer, whether mediation, conciliation or arbitration. BPSK as an out-of-court consumer dispute resolution body that carries out arbitration functions is expected to provide legal certainty in resolving consumer disputes. The decisions taken by the BPSK panel are final and binding, in accordance with the settlement method chosen by the consumer, whether mediation, conciliation or arbitration. The method used in this research is the normative legal method or also known as doctrinal legal research with a descriptive approach. The purpose of this research is to determine the process and effectiveness of resolving consumer disputes through arbitration through BPSK.